Otoferlin Deficiency in Zebrafish Results in Defects in Balance and Hearing: Rescue of the Balance and Hearing Phenotype with Full-Length and Truncated Forms of Mouse Otoferlin - Chatterjee, Paroma (Mol Cell Biol, 2015)
Sensory hair cells convert mechanical motion into chemical signals. Otoferlin, a six-C2 domain transmembrane protein linked to deafness in humans, is hypothesized to play a role in exocytosis at hair cell ribbon synapses. To date, however, otoferlin has been studied almost exclusively in mouse models, and no rescue experiments have been reported. Here we describe the phenotype associated with morpholino-induced otoferlin knockdown in zebrafish and report the results of rescue experiments conducted with full-length and truncated forms of otoferlin. We found that expression of otoferlin occurs early in development and is restricted to hair cells and the midbrain. Immunofluorescence microscopy revealed localization to both apical and basolateral regions of hair cells. Knockdown of otoferlin resulted in hearing and balance defects, as well as locomotion deficiencies. Further, otoferlin morphants had uninflated swim bladders. Rescue experiments conducted with mouse otoferlin restored hearing, balance, and inflation of the swim bladder. Remarkably, truncated forms of otoferlin retaining the C-terminal C2F domain also rescued the otoferlin knockdown phenotype, while the individual N-terminal C2A domain did not. We conclude that otoferlin plays an evolutionarily conserved role in vertebrate hearing and that truncated forms of otoferlin can rescue hearing and balance.